Book Review: vulnerable populations in the united states - Bontempi, Jean M Breny (Inquiry-the Journal of Health Care Organization Provision and Financing, 2006)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/076-630-137-691-089 tex.type: [object Object]
Keywords: book.review; dept.pch

Book Review: process evaluation for public health interventions and research - Bontempi, Jean M Breny (Inquiry, 2003)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-535-638-021-921 tex.type: [object Object]
Keywords: book.review; dept.pch

Our men are grinding out: a qualitative examination of sex ratio imbalances, relationship power, and low-income African American women's health. - Bontempi, Jean M Breny; Eng, Eugenia; Quinn, Sandra Crouse (Women & Health, 2008)
In the United States, the number of HIV/AIDS cases among women of color is increasing, with African American women now comprising 60% of all female AIDS cases. Scholars have attributed this imbalance to social factors. The aim of this study was to explore the impact that relationship power has on heterosexual women's ability to practice safer sex. Five focus groups were conducted with 24 African American women, aged 18-57 years, residing in public housing in rural North Carolina over a six-month period in 2000. Findings suggest that women maintain their independence, despite inequities in relationship power and remain strong to make a better life for their families. Recommendations are made to promote and build upon this social identity that women have in order to help them practice healthier behaviors.
8 citations (Crossref) [2023-10-31] Place: United States Bontempi, Jean M Breny. Department of Public Health, Southern Connecticut State University, New Haven, CT 06515, USA. brenybontej1@southernct.edu
Keywords: *African Americans/px [Psychology]; *Cultural Characteristics; *Poverty/eh [Ethnology]; *Power; Psychological; *Sexual Behavior/eh [Ethnology]; *Women's Health/eh [Ethnology]; Adult; African American; African American women; African Americans; Anecdotes as Topic; Cultural Characteristics; Female; Focus Groups; HIV Infections; HIV Infections/eh [Ethnology]; HIV prevention; Health Knowledge; Attitudes; Practice; Human immunodeficiency virus infection; Humans; Middle Aged; North Carolina; Poverty; Power (Psychology); Qualitative research; Questionnaires; Safe Sex; Safe Sex/eh [Ethnology]; Sexual Behavior; Sexual Partners; Sexual Partners/px [Psychology]; Sexual health promotion; Surveys and Questionnaires; United States; Women's Health; adult; article; attitude to health; behavior; cultural factor; dept.pch; ethnology; female; human; information processing; literature; middle aged; poverty; psychological aspect; questionnaire; safe sex; sexual behavior; sexuality; women's health

HIV medication adherence programs: the importance of social support. - Bontempi, Jean M Breny; Burleson, Laura; Lopez, Melissa Hofilena (Journal of community health nursing, 2004)
Since the advent of medical treatments for HIV, the promotion of adherence to these difficult treatment regimens has proven critical to disease management. Three Connecticut state-funded HIV medication adherence programs were evaluated.1 The purpose of this process evaluation was to explore and compare the goals and modality of each adherence program, assess client and staff satisfaction, and provide recommendations for the improvement of these programs. Focus group interviews with clients and individual interviews with staff were conducted at each of the programs. Interviews were transcribed, coded and analyzed with a code and retrieve method of theme identification. Focus group themes included the importance of social support on medication adherence and the "lifesaving" effect the program has had. The staff expressed that although complete adherence should be the long-term objective, more intermediate objectives should be considered (e.g., behavioral changes to increase clients' ability, self-esteem, and self-efficacy to take medications).
17 citations (Crossref) [2023-10-31] Place: United States Bontempi, Jean M Breny. Department of Public Health, Southern Connecticut State University, New Haven 06515, USA. brenybontej1@southernct.edu
Keywords: *Anti-HIV Agents/tu [Therapeutic Use]; *HIV Infections; *Health Promotion/og [Organization & Administration]; *Patient Compliance/px [Psychology]; *Social Support; Anti-HIV Agents; Attitude of Health Personnel; CD4 antigen; Connecticut; Female; Focus Groups; HIV Infections; HIV Infections/dt [Drug Therapy]; HIV Infections/px [Psychology]; Health Knowledge; Attitudes; Practice; Health Promotion; Human immunodeficiency virus infection; Humans; Male; Needs Assessment; Nursing Methodology Research; Organizational Objectives; Outcome and Process Assessment (Health Care); Outcome and Process Assessment; Health Care; Patient Compliance; Patient Education; Patient Education as Topic/og [Organization & Administration]; Program Evaluation; Questionnaires; Self Efficacy; Social Support; Surveys and Questionnaires; United States; antiretrovirus agent; article; attitude; behavior therapy; clinical article; controlled study; dept.pch; drug dose regimen; emotion; evaluation; female; health program; health promotion; human; interview; job satisfaction; male; outcomes research; patient compliance; patient education; professional practice; self concept; self esteem; self medication; social support; staff

Exploring gender differences in the relationship between HIV/STD testing and condom use among undergraduate college students - Bontempi, Jean M Breny; Mugno, Raymond; Bulmer, Sandra Minor; Danvers, Karina; Vancour, Michele (American journal of health education, 2009)
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-142-792-871-988 tex.type: [object Object]
Keywords: dept.mat; dept.pch